Emmanual, Sheila (London, 2011)
2011 "Emmanual, Sheila", 2011, HistoryTalk Sheila came to Britain from Dominica to join her husband who was a hospital porter. She was 28 years old and started working for London Transport in the early 1970s, working as a conductor on the buses. She worked on the buses for 13 years on different routes in London and she notes the badges that she received for good work- she generally enjoyed her job. Sheila took redundancy and went to work in a care home in west London and describes the type of work, including sometimes the racist abuse. She describes some of the problems she encountered in care work and retired at 60 years of age in 1999.